Study of the Performance and Determinants of Initial Coin Offering - Aissia, Dorsaf Ben; Chakroun, Alaa Eddine (Copernican Journal of Finance & Accounting, 2024)
The aim of the paper is to study the relationship between the performanceand the determinants of initial coin offering. We use panel data and multiple regressionmodels to measure the impact of the determinants of the initial coin offering on its performance. Based on a sample of 3,498 ICOs issued between January 2019 and December2023, we find that the reputation of the founding team, the quality of the informationmaterials provided to stakeholders, the market liquidity, and regulatory complianceare closely related to ICO Performance. The implications of these findings are indeedsubstantial, as they have far-reaching effects on all participants in the ICO market. Forentrepreneurs, the results highlight that success in ICOs depends not only on innovativeideas but also on effective governance and transparent communication. This underscoresthe importance of factors beyond the core technology or concept in determining the success of ICOs and emphasizes the need for comprehensive strategies thatencompass governance and communication practices.